IMPLEMENTASI ALGORITMA FUZZY C-MEANS (FCM) DALAM MEMPREDIKSI HASIL TANGKAPAN IKAN DI KOTA KENDARI - Ngii, Katharina; Sabrina, Dinar; Saputra, Rizal (Universitas Methodist Indonesia, 2023)
Almost 70% of Indonesia's region is a body of water, so production of catch fish is increasing. Fish is one of the principal ingredients that most people consume. To meet the rapidly increasing demand of fish requires predictions of fish products that can help with effective planning and decision introduction. The aim of this study is to assess the quality of predictions and provide vital information for future fish production. Fuzzy c-means (FCM) is a technique that can be used to make such predictions using data on water quality, water temperature, and fish production. Analysis using fuzzy c-means means to predict fish production in the next few years. These predictions provide information on the future volume of fish production based on water quality and water temperature data. The results of this study indicate that the method can provide accurate predictions that could be useful for the production of ongoing fish.